Control of sexually transmitted infections and prevention of HIV transmission: mending a fractured paradigm - Richard Steen; Teodora Elvira Wi; Anatoli Kamali; Francis Ndowa
Control of sexually transmitted infections (STIs) is feasible, leads to improved sexual and reproductive health and contributes to preventing HIV transmission. The most advanced HIV epidemics have developed under conditions of poor STI control, particularly where ulcerative STIs were prevalent. Several countries that have successfully controlled STIs have documented stabilization or reversal of their HIV epidemics. STI control is a public health outcome measured by reduced incidence and prevalence. The means to achieve this include: (i) targeting and outreach to populations at greatest risk; (ii) promoting and providing condoms and other means of prevention; (iii) effective clinical interventions; (iv) an enabling environment; and (v) reliable data. Clinical services include STI case management, screening and management of STIs in sex partners. Syndromic case management is effective for most symptomatic curable STIs and screening strategies exist to detect some asymptomatic infections. Presumptive epidemiologic treatment of sex partners and sex workers complement efforts to interrupt transmission and reduce prevalence. Clinical services alone are insufficient for control since many people with STIs do not attend clinics. Outreach and peer education have been effectively used to reach such populations. STI control requires effective interventions with core populations whose rates of partner change are high enough to sustain transmission. Effective, appropriate targeting is thus necessary and often sufficient to reduce prevalence in the general population. Such efforts are most effective when combined with structural interventions to ensure an enabling environment for prevention. Reliable surveillance and related data are critical for designing and evaluating interventions and for assessing control efforts.